2019
DOI: 10.1097/md.0000000000017198
|View full text |Cite
|
Sign up to set email alerts
|

HE4 as a biomarker for diagnosis of lung cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[28][29][30][31] Additionally, some of them has been identi ed as biomarkers of diagnosis of lung cancer. [32][33][34] Here, the members of WFDC family were selected to do further comprehensive analysis of their roles in lung cancer. Our results demonstrated that WFDC1 was attenuated while WFDC2 was signi cantly elevated in carcinoma tissue.…”
Section: Wfdc21p Increases In Lung Carcinoma Cells and Tissuesmentioning
confidence: 99%
“…[28][29][30][31] Additionally, some of them has been identi ed as biomarkers of diagnosis of lung cancer. [32][33][34] Here, the members of WFDC family were selected to do further comprehensive analysis of their roles in lung cancer. Our results demonstrated that WFDC1 was attenuated while WFDC2 was signi cantly elevated in carcinoma tissue.…”
Section: Wfdc21p Increases In Lung Carcinoma Cells and Tissuesmentioning
confidence: 99%
“…It has been proposed as a proteinase inhibitor with utility in the pulmonary immune system and the sperm maturation process, and it is expressed at low concentrations in various healthy tissues, including the respiratory and reproductive epithelium (27). HE4 is overexpressed in most subtypes of ovarian epithelial cancer (28) and some adenocarcinomas such as lung, endometrium and breast (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biomarkers are usually evaluated for their individual associations with the disease risks and have been widely used in the decision processes of disease diagnosis and prognosis (He et al, 2019;Leiro et al, 2019;Yokobori et al, 2019;Muller et al, 2020). Transcription factor (TF) plays a critical role in cancer cell processes, such as cell proliferation, apoptosis, migration, and regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%